Validation of a Quick Flow Cytometry-Based Assay for Acute Infection Based on CD64 and CD169 Expression. New Tools for Early Diagnosis in COVID-19 Pandemic - Comins-Boo, Alejandra; Gutiérrez-Larrañaga, Maria; Roa-Bautista, Adriel; Guiral Foz, Sandra; Renuncio García, Mónica; González López, Elena; Irure Ventura, Juan; Fariñas-Álvarez, María Carmen; San Segundo, David; López Hoyos, Marcos (Frontiers in Medicine, 2021)
Objectives Several parameters aid in deciphering between viral and bacterial infections; however, new tools should be investigated in order to reduce the time to results and proceed with an early target-therapy. Validation of a biomarker study, including CD64 and CD169 expression, was conducted. Material and methods Patients with active SARS-CoV-2 infection (ACov-2), bacterial infection (ABI), healthy controls, and antiretroviral-controlled chronic HIV infection were assessed. Whole blood was stained and, after lyse no-wash protocol, acquired by flow cytometry. The median fluorescence intensity (MFI) of CD64 and CD169 was measured in granulocytes, monocytes, and lymphocytes. The CD64 MFI ratio granulocytes to lymphocytes (CD64N) and CD169 MFI ratio monocytes to lymphocytes (CD169Mo) were evaluated as biomarkers of acute bacterial and viral infection, respectively. Results A CD64N ratio higher than 3.3 identified patients with ABI with 83.3% and 85.9% sensitivity and specificity, with an area under the curve (AUC) of 83.5%. In contrast, other analytic or hematological parameters used in the clinic had lower AUC compared with the CD64N ratio. Moreover, a CD169Mo ratio higher than 3.3 was able to identify ACoV-2 with 91.7 and 89.8 sensitivity and specificity, with the highest AUC (92.0%) Conclusion This work confirms the previous data of CD64N and CD169Mo ratios in an independent cohort, including controlled chronic viral HIV infection patients as biomarkers of acute bacterial and viral infections, respectively. Such an approach would benefit from a quick pathogen identification for a direct-therapy with a clear application in different Health Care Units, especially during this COVID pandemic.